2002
DOI: 10.1029/2001ja000245
|View full text |Cite
|
Sign up to set email alerts
|

A large‐scale traveling ionospheric disturbance during the magnetic storm of 15 September 1999

Abstract: [1] Using a comprehensive data set and model calculations, we have investigated a prominent large-scale traveling ionospheric disturbance (LSTID) observed in Japan ($37°-16°MLAT) on 15 September 1999, during a recovery phase of sequential storms. The LSTID was detected at 2300-2400 LT (1400-1500 UT) as an enhancement of the 630-nm airglow intensity (50!350 R), a decrease in the F layer virtual height (at 2 MHz, 360!200 km), an enhancement of f o F 2 (6!8 MHz), and an enhancement of GPS total electron content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 36 publications
8
106
2
Order By: Relevance
“…by Prölss and Jung (1978) and Jin et al (2008). However, strong northward winds, which were described by Shiokawa et al (2002) and Shiokawa et al (2003) analysing the geomagnetic storm on the 31 March 2001 conflict with this idea indicating that more detailed investigation is necessary. The 2-D-Fourier analyses showed that the LSTID wave fronts induced by ionospheric storms mainly propagate from North to South in Europe.…”
Section: Analyses and Discussionmentioning
confidence: 96%
“…by Prölss and Jung (1978) and Jin et al (2008). However, strong northward winds, which were described by Shiokawa et al (2002) and Shiokawa et al (2003) analysing the geomagnetic storm on the 31 March 2001 conflict with this idea indicating that more detailed investigation is necessary. The 2-D-Fourier analyses showed that the LSTID wave fronts induced by ionospheric storms mainly propagate from North to South in Europe.…”
Section: Analyses and Discussionmentioning
confidence: 96%
“…5 indicates that during the TIDs of October 2003 electrojet currents were enhanced at auroral latitudes. Shiokawa et al (2002) have associated energy deposited in the auroral oval with the initiation of meridionally propagating gravity waves. These authors calculated the amount of high latitude Joule heating and Lorentz force.…”
Section: Discussionmentioning
confidence: 99%
“…This computer software uses the satellite biases as reported by the University of Bern and calculates the receiver bias minimizing the TEC variability observed between 02:00 and 06:00 LT. TEC curves corresponding to each satellite pass and for each of the 263 receivers were then fitted to a 4th order polynomial to filter out the diurnal variability and to evaluate TEC perturbations (TECP) containing time scales of 3 h or less. Our method is different than the algorithm used by Shiokawa et al (2002) that estimates the unperturbed TEC level by removing a 2-h running average, or the procedure employed by Nicolls et al (2004) that calculates the unperturbed TEC value using a 4-h running average for several latitude-longitude bins. We claim that our derivation of the TEC perturbations reflects quite well the variability of the integrated number density due to the transit of large-scale gravity waves.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations